2006
DOI: 10.1089/end.2006.20.880
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Extracorporeal Shockwave Therapy for Peyronie's Disease

Abstract: Although a quarter of ESWT patients resorted to surgery, in the absence of other effective nonsurgical treatments, ESWT may provide a useful, safe, conservative management option. Extracorporeal shockwave therapy cannot yet be recommended as standard for Peyronie's disease, and randomized controlled studies are required to validate its efficacy and identify the subset of patients most likely to benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 20 publications
0
10
0
2
Order By: Relevance
“…Extracorporeal shockwave therapy (ESWT), which was introduced from urologists in order to destroy kidney stones, has been tested in penile fibromatosis (Evidence level Ib) [5]. Another study reported that about half of all ESWT treated patients had a significant reduction in penile angulation [6]. Given these observations in penile fibromatosis, we started to perform a randomized-controlled trial to evaluate high-energy focussed ESWT in palmar fibromatosis, Dupuytren’s contracture (DupuyShock) [7].…”
Section: Resultsmentioning
confidence: 99%
“…Extracorporeal shockwave therapy (ESWT), which was introduced from urologists in order to destroy kidney stones, has been tested in penile fibromatosis (Evidence level Ib) [5]. Another study reported that about half of all ESWT treated patients had a significant reduction in penile angulation [6]. Given these observations in penile fibromatosis, we started to perform a randomized-controlled trial to evaluate high-energy focussed ESWT in palmar fibromatosis, Dupuytren’s contracture (DupuyShock) [7].…”
Section: Resultsmentioning
confidence: 99%
“…Although initial studies failed to demonstrate any efficacy of extracorporeal shock wave therapy (ESWT) for the treatment of PD [142][143][144], more recent studies suggest a possible role of ESWL in the reduction of pain [145][146][147].…”
Section: Eswlmentioning
confidence: 99%
“…Nevertheless, ESWT is described as a nonsurgical treatment of Peyronie's diseases in humans. This disorder of the penis is characterized by dense, fibrous plaque formation in the tunica albuginea sometimes associated with calcification or ossification and clinically causing pain, distortion, and erection problems 12 . Despite the lack of conclusive evidence of effects of ESWT 13 in the treatment of Peyronie's disease, it was shown to have minimal adverse effects and to be safe.…”
Section: Discussionmentioning
confidence: 99%